How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M M; Pereira, J S; MAROCO, J; RODRIGUES, M L; RICARDO, C P P; OSÓRIO, M L; CARVALHO, I; Faria, T; PINHEIRO, C (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Comparative water relations of four Mediterranean oak species - Acherar, M.; Rambal, S. (Plant Ecology, 1992)
The water relations and responses of two evergreen (Quercus ilex L. and Q. suber L.) and two decidu- ous (S. afares Pomel. and Q. faginea Will.) Quercus species were studied under experimental conditions. Two-year old seedlings grown in 30 1. pots were subjected to a drying period during which stomatal conductance, pre-dawn potential and minimum foliar potential were measured. The results shows that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al. (1978 & 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance as described by the reciprocal function g ........ = ( -0.47 + 2.61.~bp) 1 for the evergreen oaks and g ......... (-1.94+7.39.~bp) 1 for the deciduous species. These differences between the two groups may partialy explain their geograhic distributions, and suggest general questions concerning the mechanisms which optimize water-use efficiency in Mediterranean oak species.
Keywords: mediterranean species; Quercus; Stomatal conductance; water-potential; water-stress